Photosynthesis and Rubisco kinetics in spring wheat and meadow fescue under conditions of simulated climate change with elevated CO2 and increased temperatures - K. HAKALA (Agricultural and Food Science, 2008)
Spring wheat (Triticum aestivum L.cv.Polkka)and meadow fescue (Festuca pratensis Hudson cv. Kalevi)cwere grown in ambient and elevated (700 µl l -1 )carbon dioxide concentration both at present ambient temperatures and at temperatures 3°C higher than at present simulating a future climate.The CO2 concentrations were elevated in large (3 m in diameter)open top chambers and the temperatures in a greenhouse built over the experimental field.The photosynthetic rate of both wheat and meadow fescue was 31 37%higher in elevated carbon dioxide (eCO2 )than in ambient CO 2 (aCO2 )throughout the growing season.The enhancement in wheat photosynthesis in eCO2 declined 10 13 days before yellow ripeness,at which point the rate of photosynthesis in both CO 2 treatments declined.The stomatal conductance of wheat and meadow fescue was 2336% lower in eCO2 than in aCO2 .The amount and activity of ribulose-1,5-bisphosphate carboxylase-oxygenase (Rubisco) in wheat were lower under conditions of eCO2 ,except at elevated temperatures in 1993 when there was a clear yield increase.There was no clear change in the amount and activity of Rubisco in meadow fescue under eCO2 at either elevated or ambient temperature.This suggests that adaptation to elevated CO2 at biochemical level occurs only when there is insufficient sink for photosynthetic products.While the sink size of wheat can be increased only by introducing new,more productive genotypes,the sink size of meadow fescue can be regulated by fitting the cutting schedule to growth.;